Cognitive psychology and task-based language learning - Littlewood, William (Journal of Modern Languages, 2005)
Task-based language teaching is currently much discussed as an approach to second language tcaching. This paper addresses the issue of how the system of the language is internalized in task-based learning. First it looks at what is meant when people describe an approach as ’task-based’. This serves to highlight two major dimensions, which are then discussed in relation to task-based learning. The paper goes on to look at three strands in cognitive psychology which are relevant to helping us understand how the language system is internalized in task-based learning. Finally, it suggests some pedagogical conclusions.